Implementation of mediation in the Estate Distribution Division (EDD) to resolve estate disputes - Drs Nasrul, Muhammad Amrullah; Halim, Akmal Hidayah; Zairin Zain, Anis A’fifah (Akademi Pengajian Bahasa, Universiti Teknologi MARA Cawangan Negeri Sembilan, Kampus Kuala Pilah, Malaysia, 2025)
Disputes among family members can disrupt the administration of estate if they are not properly addressed. Despite the existence of the Estate Distribution Division to cater estate administration cases, the approach by the agency does not take into account the emotional grievance suffered by the family members which tend to be the cause of family disputes. Without proper means to address family disputes, cases involving incomplete estate administration will continue to increase to the detriment of the stakeholders including the family members, beneficiaries and the government. Research found that mediation is an excellent tool in resolving family disputes in estate administration due to its flexibility and ability to address emotional issues. This paper looks into the possibility of implementing mediation in the Estate Distribution Division in addressing the family disputes in estate administration. This research employs library-based research with specific references to articles, case laws and statutes including but not limited to the Mediation Act 2012 and Small Estates (Distribution) Act 1955. Findings show that the Estate Distribution Division is perceived as a suitable administrative body to implement mediation due to its coverage of most estate cases in Malaysia. Mediation will be able to assist in the resolution of disputes, preventing adverse issues that would result in delay and incompletion of estate administration in Malaysia